Pengetahuan Pelaku Umkm Dalam Strategi Pemasaran Di Era Digital - Bella Dwi Saputri; Dwi Novaria Misidawati (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2024)
This research uses qualitative research methods whose data sources are taken from articles, books, news according to the topic of discussion and so on. Next, perform data analysis with the technical justification of qualitative descriptive analysis. The data obtained will be analyzed to gain knowledge and understanding of marketing strategies for UMKM actors in the digital age. Small and medium-sized enterprises (SMEs) have a major role in the economy of a country, especially in Indonesia, as they contribute greatly to economic growth. UMKM has a very important role in driving the economic sector in Indonesia at the middle to lower levels, some of these roles can be summarized in the following three things: [1] Promoting economic extortion; [2] Increasing the currency of the country. Role; [3] Improving the well-being of the people. It is cited in the article Kumparan Business that by March 7, 2024 there are already 27 million UMKMs using digital, and by 2024 it is targeted that UMKM using digital reach 30 million. The article also explains that the local government continues to strengthen cooperation with various electronic trading platforms (e-commerce) to financial technology companies (fintech) to be able to the target. Strategies to improve the knowledge of UMKM participants in the development of marketing in the digital age can be through training on the use of digital marketing, giving tutorials on account creation in digital media, and giving tutorals to market products through live streaming social media